Implementation of School Policy in Maintaining Environmental Care in Indonesia - Nurlila, Ratna Umi; La Fua, Jumarddin (Institut Agama Islam Negeri Kendari, 2022)
This qualitative research aims to educate and provide information to the public about the role of educational institutions in environmental care. This can be achieved by influencing people’s behavior to engage in environmental management through education in the school environment. Schools can implement programs or rules that teach students about environmental management and ensure that each student carries out and obeys the rules positively and responsibly. This research was conducted in SMAN 4 Kendari, Southeast Sulawesi, Indonesia. This school is one of the schools with an environmental vision that has been established based on government decisions. Data collection is done through observation, interviews, and documentation. The results of the study indicate that school policy in maintaining the ethical values of environmental care is done through strengthening school rules to ensure that each student is involved in managing the school environment, managing school facilities and services oriented towards environmental management, and strengthening and assisting students’ extracurricular programs in environmental management. With the approach undertaken by the school, it is expected to realize a healthy and comfortable environment and become a model in creating an eco-friendly environment school. Keywords: Character; education; environment; management; eco-friendly